Telomere Length and Vascular Phenotypes in a Population-Based Cohort of Children and Midlife Adults - Nguyen M.T.; Vryer R.; Ranganathan S.; Lycett K.; Grobler A.; Dwyer T.; Juonala M.; Saffery R.; Burgner D.; Wake M. (American Heart Association Inc., 2022)
Background: Telomere length has been inversely associated with cardiovascular disease in adulthood, but its relationship to preclinical cardiovascular phenotypes across the life course remains unclear. We investigated associations of telomere length with vascular structure and function in children and midlife adults.
Methods and Results: Population‐based cross‐sectional CheckPoint (Child Health CheckPoint) study of 11‐ to 12‐year‐old children and their parents, nested within the LSAC (Longitudinal Study of Australian Children). Telomere length (telomeric genomic DNA [T]/β‐globin single‐copy gene [S] [T/S ratio]) was measured by quantitative polymerase chain reaction from blood‐derived genomic DNA. Vascular structure was assessed by carotid intima‐media thickness, and vascular function was assessed by carotid‐femoral pulse‐wave velocity and carotid elasticity. Mean (SD) T/S ratio was 1.09 (0.55) in children (n=1206; 51% girls) and 0.81 (0.38) in adults (n=1343; 87% women). Linear regression models, adjusted for potential confounders, revealed no evidence of an association between T/S ratio and carotid intima‐media thickness, carotid‐femoral pulse‐wave velocity, or carotid elasticity in children. In adults, longer telomeres were associated with greater carotid elasticity (0.14% per 10–mm Hg higher per unit of T/S ratio; 95% CI, 0.04%–0.2%; P=0.007), but not carotid intima‐media thickness (−0.9 μm; 95% CI, −14 to 13 μm; P=0.9) or carotid‐femoral pulse‐wave velocity (−0.10 m/s; 95% CI, −0.3 to 0.07 m/s; P=0.2). In logistic regression analysis, telomere length did not predict poorer vascular measures at either age.
Conclusions: In midlife adults, but not children, there was some evidence that telomere length was associated with vascular elasticity but not thickness. Associations between telomere length and cardiovascular phenotypes may become more evident in later life, with advancing pathological changes.